An Analytical Solution of Piezoelectric Energy Harvesting from Vibrations in Steel-Concrete Composite Beams subjected to Moving Harmonic Load - Dan, Dao Sy; Diem, Nguyen Dang; Lam, Nguyen Ngoc; Hung, Le Quang (Engineering, Technology & Applied Science Research, 2024)
Steel–concrete composite beams are ubiquitous in construction, especially in bridge building. This paper addresses the harvesting of energy from a beam subjected to a moving harmonic load using analytical methods. The harvesting is performed by attaching a thin piezoelectric patch directly to the bottom surface of the steel beam. Based on the assumptions of the Euler–Bernoulli beam theory for the relationship between displacement and deformation, the differential equation for the vibration of a beam is derived using Hamiltonian principles. A theoretical formulation is presented for the problem of harvesting energy from a harmonic moving load on a simply supported beam. The dynamic responses are determined in exact form using analytical methods, and the energy harvested from the piezoelectric material layer is calculated. The influence of the speed of the load on the energy harvesting of the piezoelectric material layer is investigated in detail.